Washington Irving, The Sketch Book of Geoffrey Crayon, Gent. : le Moyen Âge aux origines - Delphine Louis-Dimitrov (Perspectives Médiévales)
Washington Irving’s Sketch Book of Geoffrey Crayon, Gent. (1819-1820), a collection of thirty-four “sketches”, essays and tales, is a founding work. It is the starting point of the American short story tradition and the bedrock of a national mythology; it also marks the first recognition of an American literary identity on the international scene. The European past, especially medieval, is yet central to the text and paradoxically becomes the cornerstone of the American literary identity here in the making. In a nation in quest for roots, ancestors and legacy, the memory of the Middle Ages is a major issue; it is a founding period which the United States strives to reappropriate. Indeed the narrator’s pseudonym, Geoffrey Crayon, hints at an implicit claim of lineage with Geoffrey Chaucer, whose presence frames The Sketch Book. Besides, the medieval hypotext underlying the Hudson Valley tales provides an idiom for the exploration of American themes dealing with the nation’s identity. Last but not least, the medieval presence contributes to the picturesque aesthetics that The Sketch Book claims, whether through the ruins in a European landscape or else through literary “associations”. This study will thus consider how the Middle Ages here turn into an aesthetic space.